1983
DOI: 10.1136/thx.38.4.284
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ultrasonically nebulised solutions for provocation testing in patients with asthma.

Abstract: The airway response to the inhalation of ultrasonically nebulised distilled water was determined in 55 asthmatic patients and 16 normal subjects. We calculated the dose of water required to induce a 20% reduction (PD20) in forced expiratory volume in one second (FEVy) by measuring the output of the nebuliser and the volume ventilated by each subject. Forty-eight of the asthmatic patients had a PD20 of 9 ml or less but three patients required as much as 24 ml. A PD20 was not recorded in the normal subjects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(98 citation statements)
references
References 10 publications
1
96
0
1
Order By: Relevance
“…It has been shown that a local increase in the osmolarity of the airway surface liquid as a result of respiratory water loss or inhalation of hypertonic saline induces bronchoconstriction in asthmatic patients (30,31). Because bronchial epithelium has both metabolic and secretory functions that mediate both the release of bronchodilators and removal of bronchoconstricting agents (32)(33)(34), it is possible that the absence of AQP5 at the luminal surface of tracheal and bronchial epithelial cells leads to altered extracellular ionic composition that could affect the release and͞or clearance of broncho-reactive substances, resulting in rapid airway responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a local increase in the osmolarity of the airway surface liquid as a result of respiratory water loss or inhalation of hypertonic saline induces bronchoconstriction in asthmatic patients (30,31). Because bronchial epithelium has both metabolic and secretory functions that mediate both the release of bronchodilators and removal of bronchoconstricting agents (32)(33)(34), it is possible that the absence of AQP5 at the luminal surface of tracheal and bronchial epithelial cells leads to altered extracellular ionic composition that could affect the release and͞or clearance of broncho-reactive substances, resulting in rapid airway responses.…”
Section: Discussionmentioning
confidence: 99%
“…The release of mediators from inflammatory cells sensitive to transient changes in airway fluid osmolality is believed to initiate AIB and HIB [25,26,41]. Mediator release in vitro [4], and in vivo [5,42] was demonstrated in response to osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…For many years it has been known that decreasing the osmolarity of the airway surface liquid by inhalation of hypotonic aerosols is a potent stimulus for airway narrowing in asthmatics (Allegra and Bianco 1980;Anderson et al 1983), aggravating the bronchial hyper-responsiveness that is a characteristic hallmark of the disease. The mechanism by which hypotonicity elicits this response is not clear, however, the effect does persist when airways are isolated (Finney et al 1987).…”
Section: Trpv Channelsmentioning
confidence: 99%